Desenvolvimento de três aplicativos educacionais para plataformas de tablets e smartphones baseados em sistemas iOS - Varjão, Ricardo Moreira (2013)
This study aimed to produce educational apps for tablets and smartphones targeted to teaching physics and mathematics that could be used both in the classroom and in informal places of learning and teaching. "Kinematics", "String" and "Equation" with themes of kinematic waves on strings and polynomial equations up to the third degree, respectively, three applications for iOS systems were developed. Until the release date at the Apple Store, between December 2011 and January 2012 up to September 2013 were made more than fourteen thousand downloads in one hundred and twelve countries spread across all continents. Comments sent to the author, both the virtual store, and through social networks, demonstrated the successful implementation of these new applications as educational tools.